Kontribusi Manajemen Kelas, Motivasi dan Lingkungan terhadap Kedisiplinan Belajar Siswa Kelas V Sekolah Dasar di Dabin III Kecamatan Godong - Riyani, Herin Verda, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, M.M., M.Pd (2016)
The purpose of this study to examine the contribution of classroom management, motivation and the environment against discipline students of class V SD in the Dabin III DistrictGodong either simultaneously or partially. The method used is survey research design correlation, this study used a descriptive pendekatankuantitatif. This study population of 154 students of class V SD is then taken through a proportional sample of 111 students sampling.teknik random data collection using the questionnaire. Data were analyzed using multiple linear regression analysis, test F-test, t-test, analysis of the coefficient of determination (R2), the contribution of predictor danuji classical assumptions. Results of the study: 1) classroom management, motivation and the environment simultaneously have contributed to discipline students of class V elementary school in the III Dabin District Godong with R2 of 78.2% level of significance value 0.000 <0.05. 2) Management classes showed significant influence on the discipline with significant value 0,000 <0,05 and the effective contribution of 19.732%. 3) Motivation showed significant influence on the discipline with significant value 0,000 <0,05 and the effective contribution of 20.735%. 4) Environment showed significant influence on the discipline with significant value 0,000 <0,05 and the effective contribution of 17.707%.